Văn học Việt Nam thế kỷ XX - Phan, Cự Đệ (Văn học, 2004)
Giới thiệu truyện ngắn của nhiều tác giả: Nguyên Ngọc, Mai Ngữ, Đinh Quang Nhã, Hồ Phương, Nguyễn Thế Phương, Dương Thị Xuân Quý, Nguyễn Quang Sáng